If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+8x-3=15x+17
We move all terms to the left:
5x+8x-3-(15x+17)=0
We add all the numbers together, and all the variables
13x-(15x+17)-3=0
We get rid of parentheses
13x-15x-17-3=0
We add all the numbers together, and all the variables
-2x-20=0
We move all terms containing x to the left, all other terms to the right
-2x=20
x=20/-2
x=-10
| -5+11g=19-13g | | 9y+21=9y+21 | | 5b-2=2b+45 | | 2x^2=16-3x | | 17/20=n/100 | | 5(m-3)=7m-9 | | x÷2=3 | | 3x23x+1=0 | | X^+x-90=0 | | 5(8-2y)=60 | | 3x(7-x)=44;-11 | | 7x-3x=44;11 | | 3k^2=k=4 | | -8+b=-3 | | 15-5x=4x+3 | | 2x+6-4x=-12 | | 2x-4+8=6x+4-3x | | -3(-2x+7)+4x=19 | | 3^x-1=7 | | x^2+4x-143=0 | | 2/3x=1/9+x | | 1/7x+7=1+2x | | 2x+6-4x=-2 | | 3(-6+5x)=87 | | 5/8+x=11/4 | | 10-2p=12 | | n/10=70/100 | | -5(x)-10=10 | | x²+1.8x-16=0 | | 9+5n=2n+6 | | 13/4=x+5/7 | | (1÷3x+4)=(5÷2.7x-2) |